EFFECTS OF L-ASCORBIC ACID AND ALPHA-TOCOPHEROL ON BIOCHEMICAL PARAMETERS OF SWIMMING-INDUCED OXIDATIVE STRESS IN SERUM OF GUINEA PIGS - BursaÄ‡-MitroviÄ‡, Marija; MilovanoviÄ‡, Dragan R.; MitiÄ‡, Radoslav; JovanoviÄ‡, Danijela; SovrliÄ‡, Miroslav M.; VasiljeviÄ‡, Perica; TomoviÄ‡, Jovica; ManojloviÄ‡, Nedeljko (African Journal of Traditional, Complementary and Alternative Medicines, 2016)
Background: The purpose of this study is to determine the effect of L-ascorbic acid and alpha-tocopherol as well as combination of these vitamins with or without exposure to physical exercise on intensity of lipid peroxidation, activity of xanthine oxidase, activity of total antioxidative system, concentration of glutathione, and activity of catalase in the serum of guinea pigs. Materials and Methods: The experimental measurements of intensity of lipid peroxidation, activity of xanthine oxidase, activity of total antioxidative system, concentration of glutathione, and activity of catalase were done in the serum of guinea pigs. The animals were exposed to the test load to achieve exhaustion and the test was terminated when the animal for the third time to sink into the water. Results: The results of this study demonstrated that endurance exercise of guinea pigs induced oxidative stress response in terms of increased lipid peroxidation and activity of xanthine oxidase in the serum of experimental animals. Our study investigated the antioxidant activity of L-ascorbic acid and alpha-tocopherol also measuring three protective markers in the serum: total antioxidant activity, content of glutathione and activity of catalase. The results obtained show that the vitamins influence the concentrations of above mentioned biochemical parameters, which points out their protective effect of swimming-induced oxidative stress. Conclusion: Single or combined administration of L-ascorbic acid and alpha-tocopherol caused significant inhibition of these markers indicating the important antioxidant activity of the vitamins. Results lead to conclude that the combined treatments with vitamins with or without exposure to physical exercise showed the clear synergistic effect.